1996
DOI: 10.1128/jvi.70.11.7833-7841.1996
|View full text |Cite
|
Sign up to set email alerts
|

The 3'-terminal consensus sequence of rotavirus mRNA is the minimal promoter of negative-strand RNA synthesis

Abstract: We used an in vitro template-dependent replicase assay (D. Chen, C. Zeng, M. Wentz, M. Gorziglia, M. Estes, and R. Ramig. J. Virol. 68:7030-7039, 1994) to identify the cis-acting signals required for replication of a genome segment 9 template from the group A rotavirus strain OSU. The replicase phenotypes for a panel of templates with internal deletions or 3-terminal truncations indicated that no essential replication signals were present within the open reading frame and that key elements were present in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
19
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 33 publications
7
19
0
Order By: Relevance
“…Our results are the first to directly demonstrate that VP1 alone lacks replicase activity. Previous studies have shown that the only essential cis-acting signal required for minus-strand synthesis in vitro is formed by the last seven nucleotides of rotavirus mRNA (21,27). Given that of the three core proteins, only VP1 specifically interacts with the 3Ј end of viral mRNA, it is likely that VP1 recognizes and binds to the cis-acting replication signal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are the first to directly demonstrate that VP1 alone lacks replicase activity. Previous studies have shown that the only essential cis-acting signal required for minus-strand synthesis in vitro is formed by the last seven nucleotides of rotavirus mRNA (21,27). Given that of the three core proteins, only VP1 specifically interacts with the 3Ј end of viral mRNA, it is likely that VP1 recognizes and binds to the cis-acting replication signal.…”
Section: Discussionmentioning
confidence: 99%
“…These investigators included as a source of replicase activity in the system either virion-derived cores or baculovirus-expressed VP1-VP2-VP3 CLPs that had been disrupted ("opened") by incubation with hypotonic buffers. Subsequently, the system was used to define the locations of cisacting signals that promote minus-strand synthesis in rotavirus gene 8 and 9 mRNAs (21,27,28). A signal essential for replication was mapped to the extreme 3Ј ends of gene 8 and 9 mRNAs and, because of the highly conserved nature of its sequence, is probably a common feature of all 11 rotavirus mRNAs (21).…”
mentioning
confidence: 99%
“…For the Reoviridae, it is not clear how genomic packaging works. It has been possible to effect minus-strand synthesis in vitro with disrupted core particles of rotavirus (8,66,83). The reaction is specific in that sequences at the 5Ј and 3Ј ends of the RNA are important in determining the extent of synthesis.…”
Section: Packaging In Other Systems With Dsrna Genomesmentioning
confidence: 99%
“…This is the first report of an infectious RNA virus recovered from an aquatic species. The prerequisite for the construction of infectious clones of IPNV was the identification of the precise 5Јand 3Ј-terminal sequences, which are crucial for replication of viral RNA (25,30). We determined the 5Ј-and 3Ј-noncoding sequences from both genomic segments of IPNV by poly(A) tailing and 5Ј RACE methods.…”
Section: Discussionmentioning
confidence: 99%
“…For example, 32 of 50 nucleotides at the 5Ј-noncoding region and 29 of 50 nucleotides at the 3Јnoncoding region between the two segments are conserved. These termini should contain sequences that are important in the packaging and replication of the IPNV genome, as demonstrated for other double-stranded RNA viruses, such as mammalian reoviruses and rotaviruses (17,25,30,34).…”
mentioning
confidence: 99%